2020
DOI: 10.3389/fnhum.2020.593806
|View full text |Cite
|
Sign up to set email alerts
|

Motor Point Stimulation in Spinal Paired Associative Stimulation can Facilitate Spinal Cord Excitability

Abstract: Paired associative stimulation at the spinal cord (spinal PAS) has been shown to increase muscle force and dexterity by strengthening the corticomuscular connection, through spike timing dependent plasticity. Typically, transcranial magnetic stimulation (TMS) and transcutaneous peripheral nerve electrical stimulation (PNS) are often used in spinal PAS. PNS targets superficial nerve branches, by which the number of applicable muscles is limited. Alternatively, a muscle can be activated by positioning the stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…A constant-current stimulation with 1-ms pulse duration was used to deliver MPS and PNS using a constant-current electrical stimulator (model DS7AH, Digitimer, Welwyn Garden City, UK). The shorter pulse duration (200-400 μs) is commonly used for MPS in clinical settings, while we (Fok et al, 2020;Nakagawa et al, 2020) as well as other groups (Charlton, 2003;Ridding & Taylor, 2001) used MPS with 1-ms pulse duration. In the present study, we used MPS with a longer F I G U R E 1 The locations of electrodes for motor point stimulation (MPS), peripheral nerve stimulation (PNS) and EMG recording from the soleus (SOL) muscle.…”
Section: Mps and Pnsmentioning
confidence: 98%
See 1 more Smart Citation
“…A constant-current stimulation with 1-ms pulse duration was used to deliver MPS and PNS using a constant-current electrical stimulator (model DS7AH, Digitimer, Welwyn Garden City, UK). The shorter pulse duration (200-400 μs) is commonly used for MPS in clinical settings, while we (Fok et al, 2020;Nakagawa et al, 2020) as well as other groups (Charlton, 2003;Ridding & Taylor, 2001) used MPS with 1-ms pulse duration. In the present study, we used MPS with a longer F I G U R E 1 The locations of electrodes for motor point stimulation (MPS), peripheral nerve stimulation (PNS) and EMG recording from the soleus (SOL) muscle.…”
Section: Mps and Pnsmentioning
confidence: 98%
“…At the same time, MPS induces an antidromic firing along the alpha motoneurons, same as PNS, which could cause the activation of a motor neuron inducing an F‐wave. For example, we demonstrated that MPS is usable to induce spinal plasticity through a paired associative stimulation protocol, suggesting that MPS induces the antidromic firing activating the motor neuron cell body (Fok et al, 2020). In our previous studies, we found motor responses at the latency of F‐wave when we applied electrical stimulation with supramaximum intensities in the soleus muscle (SOL).…”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, orthodromic drive coming from the Ia‐nerve via spinal cord would not be produced much. Thus, for MPS, antidromic drive from the motor nerve would not collide with the orthodromic drive unlike in PNS, which may be useful for intervention methods using antidromic impulse to spinal motor neuron such as paired associative stimulation 24 . On the other hand, MPS would not be useful for interventions through the Ia‐nerve such as inducing plasticity of reciprocal inhibition by repetitive Ia‐sensory stimulation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study in 22 individuals with SCI (C3–L5; AIS C–D) reported loss of MEP facilitation in the tibialis anterior muscle by prior (∼50–60 ms) conditioning stimulation of the tibial nerve, but intact facilitation with conditioning stimulation of the common fibular nerve ( 54 ). In addition, precise calculations of the CMCT have been used to design targeted paired-associative stimulation neuromodulation approaches to facilitate functional recovery after SCI ( Figure 2 ) ( 60 64 ). The paired-associative stimulation approaches are based on the Hebbian principle of associative plasticity, i.e., “neurons that fire together, wire together” ( 65 , 66 ).…”
Section: Introductionmentioning
confidence: 99%
“…Use of upper conduction time (central motor conduction time) and lower conduction time (peripheral conduction time) for targeting the stimulation to lower limb motoneuron cell bodies. Use of latencies of MEP, F-wave and M-wave for precise calculations of the conduction times [Reprinted from Fok et al, 2020 ( 64 ); reprint permitted under Creative Commons Attribution License; CC BY].…”
Section: Introductionmentioning
confidence: 99%